2007
DOI: 10.1007/s00464-007-9426-2
|View full text |Cite
|
Sign up to set email alerts
|

Endoloop-assisted polypectomy for large peduncolated colorectal polyps

Abstract: We were very interested in reading the recent paper by Katsinelos et al. [1] regarding the technique of endoloopassisted polypectomy in large pedunculated colorectal polyps. In summary, the Authors data suggest ''that although colonoscopic resection of large peduncuolated polyps using an endoloop is safe and effective, the problems encountered with this method show some of the limitations encountered with endoscopic therapy in preventing postpolypectomy bleeding when currently available instruments are used''… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
1
3
0
1
Order By: Relevance
“…Our experience with the endoloop, without bleeding, post-polypectomy syndrome, or perforation, is in accordance with the other studies reported in the literature [10,13,14], but with limitations related to large head sizes and the location of polyps. Indeed, in the historical control group, in two cases, the application of the endoloop was impossible.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our experience with the endoloop, without bleeding, post-polypectomy syndrome, or perforation, is in accordance with the other studies reported in the literature [10,13,14], but with limitations related to large head sizes and the location of polyps. Indeed, in the historical control group, in two cases, the application of the endoloop was impossible.…”
Section: Discussionsupporting
confidence: 94%
“…Katsinelos et al reported a retrospective series of 18 large pedunculated colorectal polyps that underwent endoclip-assisted polypectomy, with a median size of polyps head of 15 mm (range [11][12][13][14][15][16][17][18][19][20][21][22]. No immediate or late bleeding or perforation occurred, while one patient (5.9%) developed post-coagulation syndrome and was successfully treated conservatively [19].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The endoloop procedure was originally developed by Hachisu [15] and consists of the tightening of a loop of nylon thread around the polyp stalk. When successfully applied, this device completely stops the blood flow in the stalk [16]. An alternative method is to apply clips on the stalk before resection to stop the blood flow in the stalk [17,18].…”
mentioning
confidence: 99%
“…1 La EI es un hallazgo muy poco frecuente en nuestro medio con una prevalencia del 0,7%, pudiendo ser del 11-34% en países menos desarrollados, 2 e incluso superior al 40% en varones homosexuales y pacientes VIH positivos [1][2][3]4 . 1 La EI es un hallazgo muy poco frecuente en nuestro medio con una prevalencia del 0,7%, pudiendo ser del 11-34% en países menos desarrollados, 2 e incluso superior al 40% en varones homosexuales y pacientes VIH positivos [1][2][3]4 .…”
Section: Intestinal Spirochetosisunclassified